تقييم أداء المعاملات الإحصائية في نظم التعرف على الأنماط - حجازية محمد مصطفى (Latakia University Journal -Engineering Sciences Series, 2014)
يقدم البحث دراسةً تحليلية لتقييم أداء المعاملات الإحصائية في أنظمة التعرف المعتمدة على الواصفات البيومترية مثل الوجه واليد، فيتألف هذا البحث من مرحلتين أساسيتين؛ تتضمن المرحلة الأولى استخدام المعاملات الإحصائية لاستخلاص السمات من صور الوجه، وبصمة اليد، والمحارف العربية. ويتم تحويل الصورة الرمادية إلى صورة ثنائية ومن ثم ترميزها لتحويلها إلى شعاع أحادي البعد تمهيداً لاستخلاص خمس قيم إحصائية لكل شعاع هي: المتوسط، والوسيط، والانحراف المطلق، والانحراف المعياري ومقياس النزعة المركزية. وفي المرحلة التالية تتم الاستعانة ببرنامج الأكسل لرسم السمات المستخلصة وتمثيلها وفقاً لمخططات جاهزة مسبقاً ومقارنتها معاً، وذلك بغية تحديد قدرة هذه القيم الإحصائية على التمييز بين العينات خصوصاً المتشابهة منها. وقد تم تطبيق المرحلتين على ثلاث قواعد بيانات مختلفة تتضمن صور الوجه واليد والأحرف الأبجدية. فبينت النتائجُ أنه يمكن استخدام القيم الإحصائية للتمييز بين الأنماط حتى في حالة العينات الأكثر تشابهاً. This paper in introduces an analytic study to evaluate the performance of the statistical operators of the human recognition systems which depends on the biometrics such as face and hand. The research consists two main parts. The first uses the statistical operators to extract features from the images of face, hand, and Arabic letters. In the next part, gray scale images are transformed to binary form, then, it is encoded to one-dimensional vector as a prelude to extract five statistical attributes for each image, these attributes are: mean, median, mean absolute deviation, standard deviation, Skewness. The Microsoft excel software is used to represent and plot the extracted features via built-in charts. These charts can illustrate the ability of the statistical features to separate between samples. We depends on feature vector consists of 10 feature which are: The two experiments are applied on three databases (face, hand and Arabic letters); they show that the statistical features are very promise to recognize between patterns even in the case of too similar samples.